From Recitation to Reflection: Integrating Qur’anic Themes into Indonesian Language Learning in Islamic Primary Schools - Danial; Emha Dzia’ul Haq; Riyan Terna Kuswanto; Andi Nurindah Sari; Nurul Fauziah (Yayasan Zia Salsabila, 2025)
This study aims to explore the integration of Qur'anic values in Indonesian language learning in madrasah Ibtidaiyah and its impact on students' language skills and character development. The issues raised were how Qur'anic themes can be integrated into the Indonesian curriculum and to what extent this affects students' motivation, engagement and character building. This research used a qualitative approach with a case study method, involving NVivo-based thematic analysis and in-depth interviews with madrasah principals, teachers and parents in several Ibtidaiyah madrasahs in Southeast Sulawesi. The results showed that the integration of Qur'anic values in Indonesian language learning not only improved students' language skills, but also strengthened their moral and spiritual character. Students become more disciplined, responsible and able to link language learning with religious teachings. In effect, this approach enriches the curriculum with a holistic and interdisciplinary approach, and strengthens the link between religious and academic education. This study suggests developing a more explicit value-based curriculum, improving teachers' pedagogical competence, as well as further research with a quantitative approach to evaluate the long-term impact.